The Enzymatic Role in Honey from Honey Bees and Stingless Bees - Saba, Farooq; Zainab, Ngaini (Bentham Science Publishers, 2023)
A variety of biomolecules known as enzymes are found in honey and originated from bees and plant nectars. The plant yields nectar that aids bees in producing honey. Diastases, invertases, glucosidases, glucose oxidases and proteases are the common enzymes present in honey and highly sensitive toward UV-vis light, heat, and microwave energy. Among all enzymes, invertase and diastase have been used for assessing the freshness of honey. The enzyme's capacity to transform amylose into glucose enhances the sweetness and flavor of honey. The role of enzymatic reactions in two types of honey, based upon bee sting morphology, namely honey from honey bees (HB) and stingless bees (SB) are discussed in this review. Enzymes that act as the main ingredient in honey production are comprehensively discussed for their significance in producing good quality and therapeutic properties of honey.